2003
DOI: 10.1002/pros.10258
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen‐activated protein kinase pathway is involved in androgen‐independent PSA gene expression in LNCaP cells

Abstract: Our data suggest that enhanced androgen-independent PSA gene expression in MAP kinase-induced LNCaP cells is mediated, at least in part, by the "B" motif of the PSA promoter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…The role of the KGF/p38 pathway in inducing expression and stimulation of the AR during differentiation of the TAP may have considerable significance in androgen independent disease. It has previously been suggested that growth factors, including KGF, IGF and EGF, can activate the AR via MAPK pathways (Culig et al, 1996;Culig et al, 1994;Franco et al, 2003;Planz et al, 2001) and this pathway has previously implicated in hormone-resistant prostate cancer (Lin et al, 2001;Uzgare and Isaacs, 2004;Uzgare et al, 2003). Interestingly, we observed that KGF/p38 induced PSA production, consistent with the phenomenon of crosstalk between the KGF and AR pathways.…”
Section: Discussionsupporting
confidence: 88%
“…The role of the KGF/p38 pathway in inducing expression and stimulation of the AR during differentiation of the TAP may have considerable significance in androgen independent disease. It has previously been suggested that growth factors, including KGF, IGF and EGF, can activate the AR via MAPK pathways (Culig et al, 1996;Culig et al, 1994;Franco et al, 2003;Planz et al, 2001) and this pathway has previously implicated in hormone-resistant prostate cancer (Lin et al, 2001;Uzgare and Isaacs, 2004;Uzgare et al, 2003). Interestingly, we observed that KGF/p38 induced PSA production, consistent with the phenomenon of crosstalk between the KGF and AR pathways.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies revealed that AR function is influenced by Ras/MAP kinase interactions with AR-associated proteins (Culig et al 2005b). Elevation of PSA levels is also a p44/p42-sensitive phenomenon in androgen-independent conditions (Franco et al 2003). MDA PCa 2b cells after incubation with IL-6 showed an increase in phosphorylation of p44/p42 kinases.…”
Section: Discussionmentioning
confidence: 98%
“…ERK activation under androgen-independent conditions may contribute to the increase in PSA, an AR target gene. (68) In a mouse model of prostate cancer, activation of both ERK and p38 correlated with cell proliferation and the initiation of prostate cancer while all three major MAPKs were inactivated in advanced stage disease. (69) Similar to other tissues, there is very good correlation between JNK activation and apoptosis in prostate cancer cells; in fact, JNK activation is required for apoptosis induced by various agents in prostate cancer cells in vitro.…”
Section: Mapk Signalingmentioning
confidence: 99%